Latin American Perspectives on Law and Religion - Souza Alves, Rodrigo Vitorino (Law and Religion in a Global Context, 2020)
Ch. 1 Latin American Perspectives on Law and Religion: An Introduction -- Ch.2 Law and religion in the encounter of cultures: The normative conflicts between freedom of religion or belief and the rights of indigenous peoples in Latin America -- Ch.3 Secular or multi-confessional, that is the question: Tensions Within the Argentinean Protestantism During the Religious Freedom Act Negotiations -- Ch.4 The 2017 Proposed Law on Religious Freedom for Argentina: comparative perspectives -- Ch.5 Secular State and religious education in public schools: the Brazilian case -- Ch.6 Religious intolerance in Brazil: An analysis of the social reality -- Ch.7 Mexican Law of Religion at 27 years of the constitutional reform on religious matters -- Ch.8 Colombia as a Secular State.